A new species of Caribbean toad (Bufonidae, Peltophryne) from southern Hispaniola - Landestoy T., Miguel A.; Turner, Daniel B.; Marion, Angela B.; Hedges, S. Blair (Zootaxa, 2018)
Peltophryne armata sp. nov. is described from the South paleoisland of Hispaniola, West Indies. This is the only native toad species known to inhabit the Barahona Peninsula, Dominican Republic, in the southernmost part of Hispaniola, and it is allopatric with the widely distributed Hispaniolan toad species, P. guentheri Cochran. However, in a molecular phylogeny, the closest relative of P. armata sp. nov. is the Puerto Rican species P. lemur Cope, with which it shares a protrusive snout, large orbits, a depressed head, indistinct or absent infraorbital crests, and a long and complex advertisement call, but differs from it greatly by the very long cephalic crests, and in the massive and spinose parotoid glands that converge medially on the dorsum. The new species is similar in ecology and larval morphology to the Cuban P. florentinoi Moreno & Rivalta, but differs from it in adult morphology. The tadpole of the new species is described. Peltophryne fracta is placed in the synonymy of P. guentheri.